Bodies and boundaries in Graeco-Roman antiquity - Fögen, Thorsten; Lee, Mireille M. (Walter de Gruyter, 2009)
This volume examines the ways in which bodies, lived and imagined, were implicated in issues of cosmic order and social organisation in Graeco-Roman antiquity. It focuses on the body in performance (especially in a rhetorical context), the erotic body, the dressed body, pagan and Christian bodies as well as divine bodies and animal bodies. The articles draw on a range of evidence and approaches, cover a broad chronological and geographical span, and explore the ways bodies can transgress and dissolve, as well shore up, or even create, boundaries and hierarchies.